A new look at whale behavior: identifying multiple spatial movement patterns of Norwegian killer whales - Van Ruiten, Meghan (UiT Norges arktiske universitet, 2021)
Studying an animal’s movement patterns in both space and time can shed light on the strategies individuals use to optimize foraging and adapt to seasonal and environmental variation. Killer whales (Orcinus orca) are dynamic, apex predators inhabiting all the world’s oceans, predating and specializing on a wide variety of prey. Over the last decade, large numbers of Norwegian killer whales have been found feeding on high concentrations of over-wintering Norwegian spring-spawning (NSS) herring (Clupea harengus) in fjords of northern Norway, before often traveling to southern herring spawning grounds to continue their feeding. Smaller-scale movement patterns across habitats are less understood. This study classified Norwegian killer whale movement into five different movement modes based on satellite tracking data. To do this we used a behavioral change point analysis (BCPA) to select robust, homogeneous velocity-persistence states at intermediate scales and then modeled the net squared displacement (NSD) over time to differentiate movement patterns. The identified modes were residence/restricted area search, transiting/traveling, nomadic/wandering modes, as well as unique round trip and partial trip behavioral movements. Totally 95.4% of segments were classified into candidate movement modes. Collective whale movement showed consistent use of all classified behavioral movement modes across differing key herring associated areas suggesting the novel candidate modes proposed reflect strategies for optimal foraging. Individual variation in movement patterns suggests potential divergent foraging strategies among individuals or groups of Norwegian killer whales, and highlights the gaps in knowledge regarding the variation of smaller-scale search and dispersal movements in this species. Sequence analysis of behavioral modes reveals no clear patterns at intermediate spatiotemporal scales, suggesting environmental or prey field factors having more influence over movement decision making. This study can serve as a baseline ...